Phase diagram assessment of CaO–Al2O3–La2O3 system. (3rd July 2017) - Li, Yandong; Liu, Chengjun; Zhang, Tongsheng; Tian, Meizi; Peng, Cheng
ABSTRACT: Considering the significance of CaO–Al2 O3 –RE2 O3 (RE = rare earth) phase diagrams, the Redlich–Kister expression was employed to evaluate the binary phase diagrams of CaO–Al2 O3, La2 O3 –Al2 O3 and CaO–La2 O3 systems in the present work. Also, the activities of CaO and Al2 O3 in the CaO–Al2 O3 binary system were calculated. The phase diagram of the CaO–Al2 O3 –La2 O3 ternary system was first assessed by Kohler extrapolation method. The accuracy of calculated phase diagrams was validated by comparing with existing experimental points and the calculation results from the literature. The obtained diagrams will lay a foundation for Al-killed steelmaking process, metallurgical flux and other fields' industrial application.